2022
DOI: 10.1021/acs.nanolett.2c01768
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Power Wearable Organic Ferroelectric Device for Optoelectronic Neuromorphic Computing

Abstract: In order to imitate brain-inspired biological information processing systems, various neuromorphic computing devices have been proposed, most of which were prepared on rigid substrates and have energy consumption levels several orders of magnitude higher than those of biological synapses (∼10 fJ per spike). Herein, a new type of wearable organic ferroelectric artificial synapse is proposed, which has two modulation modes (optical and electrical modulation). Because of the high photosensitivity of organic semic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…To improve the performance of 2D photodetectors, various modulated methods have emerged, such as the construction of hybrid dimensional heterojunctions, strain engineering, gate voltage, and other local field enhancement methods . In recent years, the method of ferroelectric local field modulation has been applied in a variety of scientific fields, including superconductivity, excitons, photocatalysis, energy storage, and specially electronic devices. Ferroelectric modulation provides benefits over other techniques for multipurpose photoelectric devices, namely low power consumption and selective modulation of the background carrier concentration via ferroelectric local field effects. However, familiar ferroelectric materials (for example, PZT and PVDF) are either insulators or wide bandgap semiconductors with weak conductivity. 2D hybrid perovskites ferroelectric materials have superior photoelectric capabilities but are unstable and poisonous to heavy metals, which further limits their practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of 2D photodetectors, various modulated methods have emerged, such as the construction of hybrid dimensional heterojunctions, strain engineering, gate voltage, and other local field enhancement methods . In recent years, the method of ferroelectric local field modulation has been applied in a variety of scientific fields, including superconductivity, excitons, photocatalysis, energy storage, and specially electronic devices. Ferroelectric modulation provides benefits over other techniques for multipurpose photoelectric devices, namely low power consumption and selective modulation of the background carrier concentration via ferroelectric local field effects. However, familiar ferroelectric materials (for example, PZT and PVDF) are either insulators or wide bandgap semiconductors with weak conductivity. 2D hybrid perovskites ferroelectric materials have superior photoelectric capabilities but are unstable and poisonous to heavy metals, which further limits their practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al. [ 106 ] reported a novel wearable organic ferroelectric neuromorphic transistor (Figure 9d) with both optical and electrical modulations. The learning behavior of the device in practical problems can be simulated using a sequence of light pulses (Figure 9e).…”
Section: Categories Of Ld Optoelectronic Neuromorphic Devicesmentioning
confidence: 99%
“…This photoconductive enhancement decays rapidly after the input light is removed. Li et al [106] reported a novel wearable organic ferroelectric neuromorphic and c) LTP behaviors by intensity varied light illumination. Reproduced with permission.…”
Section: Ferroelectric Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, various optoelectronic neuromorphic devices have been studied to develop artificial visual perception systems, and realize optoelectronic neuromorphic functions [11], [12], [13], [14], [15], [16]. Optoelectronic neuromorphic computing has received increasing attention in the fields of machine learning, image processing, and visual perception [17], [18].…”
mentioning
confidence: 99%